Eco-restructuring : implications for sustainable development - Ayres, Robert U.; Weaver, Paul M. (Paul Michael), 1956- (Tokyo ; New York : United Nations University Press, 1998)
Following on from the critically acclaimed Industrial Metabolism, this study provides a significant contribution to the literature on sustainability by identifying, on a sectoral basis, the critical issues facing the world as a whole, and the technical feasibility of addressing them. A new paradigm of eco-restructuring for sustainable development is introduced, involving shifts in technology, economic activities and lifestyles needed to harmonize human activities with natural systems.
11. The restructuring of transport, logistics, trade, and industrial space use / Paul M. Weaver -- 12. National and international policy instruments and institutions for eco-restructuring / Mikoto Usui.
Includes bibliographical references and index.
Keywords: Sustainable development; Environmental policy